(untitled) (Research, Society and Development, 2021)
Introduction: The relationship between subjects, groups and institutions has been the subject of research in different areas of knowledge. In the field of Social Sciences and Health, she has contributed to understanding the social structure, the position of agents, relationships of affinity, degree of connectivity, the resources in circulation and the different capitals at stake. In the literature, the methodological proposal of Social Network Analysis emerges as a theoretical construct that has guided different researches. Objective: To present the theoretical aspects of the Social Network Analysis methodology, its characteristics, applicability and specificities. Methodology: Narrative review of the literature developed between the months of February 2019 and December 2020 in scientific publications such as books, theses, dissertations and articles, whose discussion had as object of study the methodology of social networks analysis. Results: They emerged through the analysis of the studies and were presented the historicity, the concepts, the properties, the use and the main theorists related to the Social Network Analysis methodology. The methodology allows a double quantitative and qualitative approach, contributing to the observation and appreciation of the flow of information between individuals and graphic visualization of the subjects inserted in a given field. It was possible to apprehend the relevance of the method for analyzing the social structure and how the relations influence its organization and functioning. Conclusion: It was observed that the theory has been potent for research in the area of ​​health, either by the organization of the system in networks, or by the multidisciplinary and interdisciplinary work of the actions in this field, contributing greatly to reflection on the practice and debates involving policies, norms and work process.